Prediksi Volatilitas Indeks Harga Saham Gabungan Menggunakan GARCH - Jange, Beno (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to determine the Volatility Prediction of the Indonesia Composite Index using GARCH. GARCH is a model for generating forecasts based on historical data using a function of its own past lag plus past innovations. This study uses quantitative methods. The data in this study are JKSE data for 11 (eleven) years, from 01-01-2012 to 31-12-2022. The volatility prediction is carried out for a year, namely in 2022. The results of this study indicate that the prediction accuracy is quite good with a MAPE of 17.26 percent. It was also found that volatility was quite pronounced, which rose significantly in May 2022 due to the effect of the absence of restrictions on the Eid holiday and decreased significantly in July 2022 due to the government extending the implementation of restrictions on community activities (PPKM) throughout Indonesia and dropping even more sharply due to the government increasing prices of Pertalite in September 2022.